2013
DOI: 10.1103/physrevc.88.064314
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous fission lifetimes from the minimization of self-consistent collective action

Abstract: The spontaneous fission lifetime of 264 Fm has been studied within nuclear density functional theory by minimizing the collective action integral for fission in a two-dimensional quadrupole collective space representing elongation and triaxiality. The collective potential and inertia tensor are obtained self-consistently using the Skyrme energy density functional and density-dependent pairing interaction. The resulting spontaneous fission lifetimes are compared with the static result obtained with the minimum-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
123
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(132 citation statements)
references
References 40 publications
8
123
1
Order By: Relevance
“…As it was shown years ago [88,89] and also in recent publications [29,30,68,90] the minimisation of the reduced action integral instead of the potential energy leads to larger fission probabilities or equivalently to shorter fission HLs. The latter are generally reduced by one to two orders of magnitude in comparison to statically calculated HLs.…”
Section: Fission Dynamicsmentioning
confidence: 80%
See 2 more Smart Citations
“…As it was shown years ago [88,89] and also in recent publications [29,30,68,90] the minimisation of the reduced action integral instead of the potential energy leads to larger fission probabilities or equivalently to shorter fission HLs. The latter are generally reduced by one to two orders of magnitude in comparison to statically calculated HLs.…”
Section: Fission Dynamicsmentioning
confidence: 80%
“…The dynamic treatment of some internal degrees of freedom like e.g., pairing gap (see [91] and the very recent paper [70]) or particle number fluctuation parameter λ 2 in Lipkin-Nogami pairing model [68,29,30] seems to be more significant than a similar treatment of space-type deformation coordinates described above. While the latter is already well known to be similar for all instances the former depends on the considered nucleus.…”
Section: Fission Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The important milestone was a recent paper [19], which demonstrated that predicted SF pathways strongly depend on the choice of the collective inertia and approximations involved in treating level crossings. The main objective of the present work is to elucidate the role of nucleonic pairing on SF by studying the dynamic fission trajectories of 264 Fm and 240 Pu in a four-dimensional collective space.…”
mentioning
confidence: 99%
“…[19]. In the semi-classical approximation, the SF half-life can be written as [23,24] T 1/2 = ln 2/(nP ), where n is the number of assaults on the fission barrier per unit time (here we adopt the standard value of n = 10 20.38 s −1 ) and P = 1/(1 + e 2S ) is the penetration probability expressed in terms of the fission action integral,…”
mentioning
confidence: 99%